2010
DOI: 10.1007/s11661-010-0389-x
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Neutron Diffraction Study of the Bauschinger Effect in B2 Structured CoZr

Abstract: A combination of in-situ neutron diffraction and elastoplastic self-consistent (EPSC) modeling have been used to elucidate the role played by intergranular stresses in the Bauschinger effect in B2 structured CoZr at room temperature and 423 K (150°C). It is shown that, when insufficient slip modes are present to accommodate arbitrary strains, the large intergranular stresses built up due to inhomogeneous plastic deformation are responsible for the observed Bauschinger effect. Upon the onset of secondary deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The procedure is illustrated by an example: Single crystals of CoTi and CoZr intermetallics of the B2 type, CsCl structure, can only deform plastically if they are oriented for a particular slip-mode such that <001>{110} slip systems become activated [28,29,30]. When deformed in other orientations they respond with early brittle fracture [31,28].…”
Section: Large Reciprocal Space Coverage With High Angular Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure is illustrated by an example: Single crystals of CoTi and CoZr intermetallics of the B2 type, CsCl structure, can only deform plastically if they are oriented for a particular slip-mode such that <001>{110} slip systems become activated [28,29,30]. When deformed in other orientations they respond with early brittle fracture [31,28].…”
Section: Large Reciprocal Space Coverage With High Angular Resolutionmentioning
confidence: 99%
“…This would not be sufficient for the generalized criterion of the number of slip systems required to accommodate arbitrary strains in polycrystalline specimens [32,33]. Despite the limited number of slip systems in the soft slip-mode, the polycrystalline specimens of these alloys exhibit significant ductility [29,30]. Lattice strain measurements by in-situ neutron diffraction experiments supported by polycrystal plasticity modeling have shown that during deformation of polycrystalline CoTi and CoZr the slip systems of the soft mode are accompanied by the activation of <110>{110} and/or <111>{111} slip systems [29].…”
Section: Large Reciprocal Space Coverage With High Angular Resolutionmentioning
confidence: 99%
“…As a first approach, in case of tensile tested CoTi and CoZr B2 structure ordered alloys presented in chapter 4, possible dislocation types were grouped into smaller groups based on the physical criteria of plastic deformation of the B2 alloy system and earlier TEM observations [Wollmershauser et al 2010;Mulay et al 2011;Mulay & Agnew 2012]. Care was taken to deliberately mix different Burgers vector types in each group.…”
Section: Fitting Fractional Dislocation Densities By Monte-carlo Type...mentioning
confidence: 99%
“…One set of experiments was conducted with in-situ lattice strain monitoring, and the other set was conducted without the neutron di↵raction monitoring, referred to here as ex-situ. The ex-situ experiments were conducted to failure and were used to illustrate the changes in ductility between the charging levels, while the in-situ experiments will reveal any changes in the onset of the di↵erent deformation The change in lattice spacing during deformation for di↵erent hkl di↵raction peaks provides insight into the plastic deformation mechanisms active, and when used in conjunction with micromechanical modeling, can be used to quantify the relative strengths, as seen in work by the current authors on uranium [30,31], beryllium [66], zirconium [67], stainless steels, intermetallics [68], and magnesium [48]. Here, the measurements are used to show any changes in deformation mechanisms between the di↵erent levels of hydrogen charging.…”
Section: Mechanical Deformation Experimentsmentioning
confidence: 97%